Study Of Orthopaedic Problems In A Rural Area In Relation To Their Effect On Economy Of the Patients & Availability Of the Treatment - Sandu Hardas Singh; Sudesh Arora; Manmohar Singh; Varinder Mohan (Wolters Kluwer Medknow Publications, 1988)
A door-to-door survey of 10,000 populations was carried out in a rural area. Four hundred sixty one (46.1/1000) persons had orthopedic problems. Three hundred sixty three (78.74%) patients continued the same job in spite of the orthopedic problem. Eight (1.73%) patients modified the job and 2 (0.43%) had to change the job. It affected the earning capacity of 19(4.12%) patients. Seventy-five (16.26%)patients sought treatment from Hospital/qualified doctors. One hundred forty six (31.67%) patients received treatment from unqualified persons. Two hundred forty (52.06%) patients did not receive treatment at all. Three hundred thirty two (72.0%) patients required conservative treatment. Fifty (10.84%) required continuing the same treatment they were taking. Twenty-five (5.42%) required no treatment at the of survey.